Homework Help

a. The system that consists of y=-3x+6 and y=x^2-4x is a linear-quadratic system. How...

user profile pic

samanthahuber | Student, Undergraduate | eNoter

Posted May 10, 2013 at 8:25 PM via web

dislike 2 like

a. The system that consists of y=-3x+6 and y=x^2-4x is a linear-quadratic system. How would you solve the system algebraically? Graphically?

b. Solve the system in part (a).

Tagged with math

3 Answers | Add Yours

user profile pic

chainrule | eNoter

Posted May 10, 2013 at 8:55 PM (Answer #1)

dislike 1 like

Use the method of substitution to detmine when the two formulas have an intersection point.

X^2-4x=-3x+6

Solve for x by moving all terms to one side and causing the other side to be equal to zero.

 

X^2-7X+6=0 

 

(X-6)(X-1)=0

 

.:. The system is solved when X equals 6 or 1.

 

user profile pic

oldnick | Valedictorian

Posted May 10, 2013 at 8:56 PM (Answer #2)

dislike 1 like

`-3x+6=y`   (1)

`y=x^2-4x`    (2)

From (1) and (2):

`y=3(2-x)`                  (3)

`y=(2-x)^2-4`           (4)

comparing (3) to (4):

`3(2-x)=(2-x)^2-4`  (5)

set:   `2-x=z`                (6)

`z^2-3z-4=0`

`Delta= 9-4(-4)=25 >0`

System has two different real solution:

 `z=(3+-sqrt(25))/2`

```z_1=4`   `z_2=-1` 

So  from (6):        `x_1= -2`    `x_2=3`

Afterword:           `y_1=12`       `y_2=-3`

Graph show us:

Geomethric meaning  is that the two curves: (Red line `y=x^2-4x` , blue line :  `y=-3x+6` )

at the point  `P(-2;12)` , and `Q(3;-3)`

 

 

user profile pic

violy | High School Teacher | (Level 3) Assistant Educator

Posted May 10, 2013 at 11:17 PM (Answer #3)

dislike 0 like

Plug-in -3x + 6 on the secon equation in eplace of y. 

`-3x + 6 = x^2 - 4x`

put all the terms on left side. Remember to change the sign of the term you are moving to the other side. 

`-3x + 6 - x^2 + 4x = 0`

Combine like terms.

`-x^2 + x + 6 = 0`

Multiply both sides by -1 to make the leading coefficient positive.

`x^2 -x -6 = 0`

Factor the left side. 

`(x - 3)(x + 2) = 0`

Equate each factor to zero, and solve for x.

`x - 3 = 0 ; x + 2 = 0`

`x = 3 ; x = -2` 

Solve for y for both values of x.

We can use the first equatiop. 

`y = -3(3) + 6 ; y = -3(-2) + 6`

`y = -9 + 6; y = 6 + 6`

`y = -3 ; y = 12`

Thefore the system is {(3, -3), (-2, 12)}.

Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes